2019
DOI: 10.1108/k-12-2018-0696
|View full text |Cite
|
Sign up to set email alerts
|

Prosumption: bibliometric analysis using HistCite and VOSviewer

Abstract: Purpose Over the past decade, the term prosumption (denoting simultaneous consumption and production) has exhibited a dramatic increase in frequency of use in publications in the social sciences and business studies. This paper aims to explore the current state of research into prosumption, particularly related to marketing. Design/methodology/approach This study systematically reviews papers on prosumption extracted from the Web of Science, using two bibliometric analyses on 20 years of data: citation count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 97 publications
0
105
0
19
Order By: Relevance
“…By visualizing this network structure, we can figure out the relationship between the ASJC codes [ 33 , 34 ]. In this study, we used the modularity-based clustering method from VOSviewer (Leiden University, Leiden, The Netherlands, Version 1.16.15) [ 35 ]. We chose this methodology because a prior study showed that results yielded by the VOSviewer clustering technique are more precise and consistent than those yielded by k-means, which does not divide the largest cluster into smaller clusters (i.e., that have nodes which are closer to each other; see the comparison results of other clustering algorithms in supplementary Table S1 and Figure S1 ) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…By visualizing this network structure, we can figure out the relationship between the ASJC codes [ 33 , 34 ]. In this study, we used the modularity-based clustering method from VOSviewer (Leiden University, Leiden, The Netherlands, Version 1.16.15) [ 35 ]. We chose this methodology because a prior study showed that results yielded by the VOSviewer clustering technique are more precise and consistent than those yielded by k-means, which does not divide the largest cluster into smaller clusters (i.e., that have nodes which are closer to each other; see the comparison results of other clustering algorithms in supplementary Table S1 and Figure S1 ) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…By visualizing this network structure, we can figure out the relationship between ASJC codes. The VOSViewer (Version 1.6.15, Leiden University, Leiden, The Netherlands) software was used as a network structure visualization tool and is widely used in bibliometric analyses, especially in cluster analyses [29]. The first step for constructing a map is to calculate the similarity matrix as input.…”
Section: Clustering Network Visualization Defining Virology-relatedmentioning
confidence: 99%
“…To further explore trends and hot topics in the analyzed research field, we conducted co-citation analysis using VOSViewer. Bibliometric analysis of co-citation is a meta-analytical method that shows the interconnections between research articles and topics (Shah, Lei, Ali, Doronin, & Hussain, 2019). This analysis yielded three clusters ( Figure 5).…”
Section: Document Co-citation Analysismentioning
confidence: 99%